HBR's 10 must reads on teams. - Jon R. Katzenbach and Douglas K. Smith (Boston, Mass. : Harvard Business Review Press, 2013)
We've combed through hundreds of articles in the Harvard Business Review archive and selected the most important ones to help you assemble and steer teams that get results.
Includes index.
Keywords: Teams in the workplace